ANALYSIS OF DETERMINANTS OF LITERACY AND NUMERACY ACHIEVEMENTS OF ELEMENTARY SCHOOL STUDENTS: A CASE STUDY BASED ON EDUCATION REPORTS AT SDN 2 MANGGARMAS - nurul mutmainah; ngurah ayu nyoman murniati; Supandi (SOSIOEDUKASI, 2026)
This research was driven by the low cognitive reasoning abilities of elementary school students, despite administrative scores showing a positive trend. The objective of the study was to analyze the determinants of literacy and numeracy achievement at SDN 2 Manggarmas through Education Report Card data. The research method used a descriptive qualitative case study with data triangulation techniques involving the 2024–2025 Education Report Card document, interviews, and observations. The results showed a 23.62-point increase in numeracy scores (reaching 84.98) and the successful elimination of 0% of students below the standard. However, a significant Cognitive Gap was found between the ability to know (89.13) and reason (74.60), as well as disparities in the geometry domain (77.93). The conclusion suggests that the quantitative increase is influenced by adaptive instructional leadership, but further pedagogical transformation is needed to improve the depth of students' reasoning (L3).